(untitled) (Globalization and Business, 2023)
Tax administrations play a big role in terms of the economic development of the country. Each reform or change implemented by them leave a significant imprint on shaping the business environment. Without adopting a fair tax policy, progress in business, as well as in the economy is unachievable. Fulfillment of commitments under the cooperation with EU represents the state priority. Respectively, the best model of European practice is being established in 2021, further promoting the cooperation between Georgia and the EU to move to another level. Considering the abovementioned circumstances, the value-added taxable objects have been substantively changed since 2021 in Georgia. The amendments aim to protect the tax payers’ rights, improve the tax regime and approximate it to the European Standard to the maximum extent possible. As a result of qualitative research, the expectations both of field experts and business sector representatives towards the amendments made to value-added tax since 2021 have been analyzed through an in-depth interview. The research was aimed at defining the further role of the amendments from the perspective of economic development. The impact of implemented reforms on the development of the country’s economy was assessed as the research object, and the amendments made to the Tax Code in 2021 and the mechanisms of its functioning were determined as the subject of the research.